Impact of the business environment on output and productivity in Africa - El-hadj Bah; Lei Fang (Federal Reserve Bank of Atlanta, 2011)
We develop a general equilibrium model to assess the quantitative impact of distorting institutions and policies related to the poor business environment in 30 sub-Saharan African countries. A subset of the distortions - namely, regulation, crime, corruption, and poor infrastructure - is modeled as a tax on output. From the data, we find that, on average, firms in Africa lose a fifth of their sales as a result of those distortions. On the other hand, low access to credit affects the reallocation of resources across firms and capital formation. We find that the quantitative effects of these areas on the business environment are large. They lead to decreases in the range of 40 to 77 percent for output and from 18 to 44 percent for total factor productivity. Overall, the distortions explain about 67 percent of the variation in income per worker relative to the United States.
Keywords: O16; O47; L23; 330; entry business environment; investment climate; African development; productivity